Virulent Bacteria as Inflammatory and Immune Co-Factor in Colon Carcinogenesis: Evidence From Two Monozygotic Patients and Validation in CRC Patient and Healthy Cohorts - Sobhani, Iradj; Bergsten, Emma; Charpy, Cecile; Chamaillard, Mathias; Mestivier, Denis (Frontiers in Cellular and Infection Microbiology, 2021)
Colorectal carcinoma (CRC) is a common disease incidence of which is increasing according to western style of life; it remains of poor prognosis. Western nutriments are presumed inducing mild inflammation within the colonic mucosa resulting in the accumulation of DNA alterations in colonocytes through a multistage carcinogenesis process. This suggest that most CRCs are related to the environment. Of interest, fecal microbiota composition has been shown yielding novel approach regarding how the environment changes may impact health and disease. Here, we compare whole shutgun metagenomic gut microbiota of two monozygotic twin sisters, one of whom suffering from an advance colorectal tumor with a profound disequilibrium of the composition of the gut microbiota due to the overexpression of virulent bacteria such as E. coli, Shigella, and Clostridium species in the colon cancer patient’s feces contrasting with low level of bacterial species such as Faecalibacterium and Akkermansia usually enriched in the healthy adults’ microbial flora. The disequilibrium in microbiota of the CRC patient’s feces as compared to her monozygotic twin sister is linked with inflammatory and immune cell infiltrate in the patient’s colonic tissue. We speculate on the role of microbiota disequilibrium on the immune tolerant cell infiltrate within CRCs.